Menampakkan Corak Biru Kekristenan Indonesia: Sebuah Perspektif Ekoteologi - Maggang, Elia (Asosiasi Teolog Indonesia, 2019)
This paper seeks to interpret that which is blue of Indonesiaâ€”the largest archipelagic nation in the worldâ€”by way of proffering for Indonesian Christianity a range of blue hues (corak biru) following an ecotheological perspective. I start by discussing ecotheology and its contribution within Christianity to illustrate how this sub-discipline becomes a â€œbrushâ€ that for Christianity can render such blue hues. This is followed by a discussion on why and how a responsive ecotheology to the environmental/marine ecosystem crisis could render as â€œblue paintâ€ for that subdisciplinary brushâ€”a blue ecotheology (ekoteologi biru). To accomplish this, both Christianityâ€™s abject appraisal of the sea, as well as Christianityâ€™s own blue-hued anthropocentrism (corak biru antroposentrisme), are parsed and addressed in turn by the paradigm of a community of creation as â€œsketch.â€ These discussions summarily affirm the conviction that the sea must be considered and treated not as an object of human exploitation but as a proper subject working to support the life that is common among all of Godâ€™s animate creation. Humankind and the sea itself, alike, participate in that life. The spectrum of blueness I propose to be displayed across the â€œcanvasâ€ of Indonesian Christianity is this: to be sea-friendly in both outlook and attitude, in ways that safeguard the seaâ€™s ongoing involvement in life. To conclude, this paper invites Indonesian Christianity to put the full array of its blue hues on display within both theological discourse and its activities as the church.